Studies on the agamic reproduction in Sporobolus indicus - Febles, Gustavo; Padilla, C?sar; Achan, Geovanis (Cuban Journal of Agricultural Science, 2013)
An experiment was conducted for two years to know the existence of agamic reproduction in Sporobolus indicus. The analysis of variance was carried out to simple classification model, with six repetitions corresponding to the samplings of each year. The diameter of the bunch, as well as the number of alive and dead tillers, were measured. Each year was divided into four periods: February-April, May-July, August-October and November-January. No significant differences were found in both years during the first three periods. Significant differences (P < 0.05) were found in the number of alive and dead tillers, with a tendency to diminish both. There were no differences in the diameter of the bunch. It is concluded that, in this weed, the agamic reproduction may be considered as an element of accessory dispersion of the gamic reproduction or as a process of slow dissemination, translated into an invasion in a prolonged period of time. Key words: Sporobolus indicus, wiregrass, agamic reproduction